Effect of acute Massage on delayed-onset muscle soreness - Drake, S. M.; Keating, S.; Weir, J.; Whitehead, M. T. (The Sport Journal, 2012)
The purpose of this study was to investigate the effects of acute massage on delayed-onset muscle soreness. A total of 20 subjects (5 men and 15 women; mean age 24 ± 3 years; height 1.7 ± 0.1 m; weight 71 ± 1.4 kg) were randomly assigned to either a massage treatment (MAS, n = 8) or control (CON, n = 12) group. Following preliminary data collection, muscle soreness was induced to both groups using identical protocols. The MAS group received a 10 min massage immediately following the muscle soreness protocol where the CON group did not. Data collected included signals from electromyography (EMG), mechanomyography (MMG), perceived muscles soreness, muscle circumference, and muscle torque. Data were collected for each subject prior to and on days 1, 2, 3, and 7 following the intervention. Repeated measures analysis of variance was used to determine significant differences in the research variables between the groups with p = 0.05. A significant interaction was noted in MMG frequency during isokinetic muscle actions but all other data showed no significant interactions. Based on these data massage may not be beneficial following exercise that induces delayed onset muscle soreness.